Problem-based learning and case-based learning: which is more effective for fostering mathematical connection? - Erlinda Rahma Dewi; Arifta Nurjanah (Program Studi Magister Pendidikan Matematika FMIPA Universitas Negeri Yogyakarta, 2022)
Problem-Based Learning (PBL) and Case-Based Learning (CBL) are two typical learning approaches that involve problem-solving activities, likely to encourage students' mathematical connection abilities. This study aimed to describe the differences in mathematical connection ability between students studying with the PBL and those who used the CBL approach. A quasi-experiment with a pretest-post-test non-equivalent group design was conducted for the purpose. The data collection method was non-routine problems about mathematical connections. The data was analyzed using inferential statistics. Paired sample t-tests adopted were to examine the difference between pretest and post-test data in each experimental class, and independent sample t-tests were to verify the difference in the effectiveness of the two learning approaches. The results showed that the PBL and CBL approach enhanced mathematical connection ability. However, there was no significant difference in the mathematical connection ability between students who studied with the PBL and CBL approaches. The results, furthermore, suggest teachers construct appropriate learning to foster mathematical connection ability.